Radiation biology of Eldana saccharina Walker (Lepidoptera: Pyralidae) - Walton, Angela Jasmin (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MSc (Conservation Ecology and Entomology))--University of Stellenbosch, 2011.